2010
DOI: 10.1889/jsid18.5.368
|View full text |Cite
|
Sign up to set email alerts
|

Effects of color and background luminance on minimal legible size of dynamic Chinese characters presented on a LCD monitor for low‐vision and normally sighted users

Abstract: Abstract— The effects of velocity (3, 5, and 7 cm/sec), stimulus color (red, green, and blue), and background luminance (20–80% white, in increments of 15%) on minimal legible size of dynamic Chinese characters, were examined. Participants were divided into low‐vision, severely myopic, and normal‐vision groups. They were asked to recognize the stimulus Chinese characters, which were presented with varying velocity on a screen. Analysis showed that the minimal legible size was significantly greater for those in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
1
1
0
Order By: Relevance
“…Statistically signi cant variations in the weighted score suggested that as distance increases, the recognition rate for highbrightness colors decreases, while low-brightness colors consistently receive higher scores. It is noteworthy that, distance did not produce a signi cant effect on the recognition of green [51] Furthermore, other studies have also found that the minimum discriminable size for lowbrightness backgrounds exceeds that for high-brightness backgrounds [29] , suggesting better recognition for low-brightness colors, which is consistent with our ndings. The research by Ying Li further indicated that as observation distance increases, the discriminability of colors decreases, while the perception of black and white by visually impaired individuals relatively improves [9] , providing support for our ndings.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Statistically signi cant variations in the weighted score suggested that as distance increases, the recognition rate for highbrightness colors decreases, while low-brightness colors consistently receive higher scores. It is noteworthy that, distance did not produce a signi cant effect on the recognition of green [51] Furthermore, other studies have also found that the minimum discriminable size for lowbrightness backgrounds exceeds that for high-brightness backgrounds [29] , suggesting better recognition for low-brightness colors, which is consistent with our ndings. The research by Ying Li further indicated that as observation distance increases, the discriminability of colors decreases, while the perception of black and white by visually impaired individuals relatively improves [9] , providing support for our ndings.…”
Section: Discussionsupporting
confidence: 92%
“…Bin Cheng et al introduced a visual system and instructional design tailored for those with low vision and blindness in indoor environments, emphasizing the importance of standardized text spacing, graphic size, and color brightness [28] . Huang, K.-C. delved into the effects of color and background brightness on LCD screens for individuals with low vision, with experimental results underscoring the importance of electronic text information and icon design for visually impaired individuals [29] . Baker et al identi ed the shopping requirements of visually impaired individuals and proposed a color design approach [30] .…”
Section: Introductionmentioning
confidence: 99%